HUBUNGAN ANTARA INTENSITAS PENGGUNAAN SMARTPHONE DENGAN KESEHATAN MENTAL MAHASISWA - Nelsy Kambuno Losong; Rudangta Arianti (Universitas Muhammadiyah Metro, 2026)
One technological development whose use continues to increase is the smartphone. Smartphones offer many features and their use has various impacts that are popular among various groups, including students. The purpose of this study is to determine the relationship between the intensity of smartphone use and the dimensions of mental health, emotional well-being, social well-being, and psychological well-being. This study uses a quantitative approach with a correlational design. This study involved 59 respondents, and data was collected by sending a Google Form link via WhatsApp. Measurements were taken using a smartphone usage intensity scale developed by the researcher based on Ellison, N. B. et al.'s (2007) Intensity of Facebook theory and a mental health scale, namely the Mental Health Continuum – Short Form (MHC-SF) by Keyes (2002), which has been adapted into Indonesian. The results of the study found that there was no significant relationship between smartphone usage intensity and the mental health dimensions of emotional well-being and social well-being. However, there was one dimension of psychological well-being in the environmental mastery component that correlated with smartphone usage intensity, with a correlation value of 0.267 and sig. (p < 0.05).